Thermal Response Characterisation of First-order Fibre Bragg Gratings in Indium Fluoride Fibre - Chiamenti, Ismael; Elsmann, Tino; Reupert, Aaron; Kara, Oguzhan; Becker, Martin; Wondraczek, Lothar; Chernysheva, Maria (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Mid-infrared laser systems, particularly fibre-based, found applications in different fields, e.g. monitoring polluting gases and medical diagnostics and treatment [1]. Fluoride-based fibres have been applied as a fundamental component to build Mid-infrared fibre lasers due to their broadband transmission (up to 5.1 m for indium fluoride-based (InF 3 ) fibres [2] ), and ability to host several rare-earth dopants [1], [3]. The lack of fibre-based components, especially cavity mirrors, has led to the application of bulk elements in fibre laser systems. The usage of such elements comes with the problem that they cannot protect delicate soft-glass fibre facet from the damage caused by high pump power radiation or high-intensity laser generation [4]. Fibre Bragg gratings (FBGs), in these regards, provide the desired solution. Beyond that, recent works have numerically shown their potential to improve temperature, strain and pressure sensing using FBGs in soft glass fibres instead of state-of-the-art FBGs in silica fibres [5]. This work presents the inscription of a first-order Bragg grating in a InF 3 -based fibre. FBGs' spectral characteristics, thermal annealing, temperature response and stability ave been investigated.
CRIS-Team Scopus Importer:2023-04-20